Prevalence and Risk Factors for Hypertension in Adansi South, Ghana: A Case for Health Promotion - Duah, Amos F.; Werts, Niya; Hutton-Rogers, Laurencia; Amankwa, David; Otupiri, Easmon (SAGE Open, 2023)
This is an article published in SAGE Open, October-December 2013: 1–5; DOI: 10.1177/2158244013515689